Pemulihan dalam Pemberian Kompensasi terhadap Anak Korban Bulyying Disekolah - Putri Ramadhani Rangkuty; Herna Adelia Br Simamora; Faiz Abdul Aziz Sitorus Pane; Muhammad Riyan Prasetia; Muhamad Iqbal Parinduri (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This research aims to analyze, examine, and identify the forms of legal protection available for child victims of bullying, as well as to assess government measures in providing compensation to these victims based on Indonesia’s ius constituendum framework. In recent years, bullying cases involving minors have significantly increased, leaving victims unable to defend themselves. The primary issues addressed in this study concern the legal protection afforded to child victims of bullying and the manner in which the government provides compensation in accordance with the envisioned future law (ius constituendum) in Indonesia. This study employs a normative legal research method, relying on the examination of legal materials. The approach used is the statute approach, referring to relevant laws and regulations. The findings reveal the types of legal protection accessible to child victims of bullying and the measures that the government may implement to provide compensation in alignment with Indonesia’s aspirational legal framework.